(untitled) (Ameghiniana, 2013)
The presence of the genus Coelodus is recorded for the first time in Argentina. These rernains are assigned to a new species C. toncoensis and were found in the upper section of the Yacoraite Formation in the province of Salta. A detalled description of the splenial and vomerine dentitions are given, and their relationships with other european and north american species are discussed. The faunal association of both el Molino and the Yacoraite formations is briefly described. The cronological distribution of the genus Coelodus is mentioned, and consequently an Upper Cretaceous age for these formations is accepted. The presence of the pycnodont fish could well be a paleoecological evidence of a marine environment.